Longitudinal Associations Between Cybervictimization and Adolescent Sleep Problems: The Role of Anxiety and Depressive Symptoms - Chen, Yuanyuan (Journal of interpersonal violence, 2023)
Adolescents who have experienced cybervictimization are at risk for sleep problems. However, there is a gap in knowledge about the mechanism that would explain this link. The study used a longitudinal design to test if cybervictimization predicted adolescents' sleep problems 6 and 12 months later, and whether these patterns could be explained in part by emotional distress in response to the victimization. Participants were 1987 Chinese adolescents (56.1% males) ages 10 to 14 (M = 12.32, SD = 0.53) at baseline. Data were collected over the course of 1 year, in three waves 6 months apart. The adolescents completed questionnaires regarding cybervictimization, sleep problems, depressive symptoms, and anxiety symptoms at all three time points. Autoregressive cross-lagged models showed that cybervictimization predicted later sleep problems after controlling for traditional peer victimization, and anxiety and depressive symptoms mediated this link. Multivariate latent growth models showed that the developmental trajectories of cybervictimization, sleep problems, anxiety symptoms, and depressive symptoms were related in complex ways over time. Measures of study variables were self-reported, and generalizability may be limited by a sample of adolescents from school in China. These results are important because of their implications for prevention and treatment of adolescents’ sleep problems evoked by cybervictimization.